Basis Epistemologis KH Afifuddin Muhajir Dalam Mengkontruksi Moderasi Beragama Dalam Bidang Fiqh Tata Negara - Ahmad Muzakki; Masdar Hilmy; Roibin (Asy-Syari’ah : Jurnal Hukum Islam, 2024)
The Islamic constitutional system is important to study to describe the nature of the teachings about the state system that must be followed and applied. The purpose of this study is to provide readers with an understanding that Islamic law can respond to contemporary problems related to state administration through the study of fiqh and ushul fiqh developed by classical and contemporary scholars and to explain the epistemological basis of KH Afifuddin Muhajir in constructing religious moderation in the field of state administration fiqh. The results of this study indicate that KH Afifuddin Muhajir's thoughts on the constitutional system are based on sources of Islamic law that are muttafaq `alaih and mukhtalaf fiih. The important aspects of state administration in his view include no standardized system and form of state in Islam, freedom in making the mechanism of appointing leaders and the application of state law can be implemented substantively, comprehensively and conditionally. For researchers who want to develop research with the same theme, it can be developed by comparing KH Afifuddin Muhajir's thoughts with Western thoughts and Middle Eastern scholars related to the state system.